A computational framework for dynamic soil-structure interaction analysis - Sribalaskandarajah, Kandiah (My University, 1996)
This dissertation presents: (i) a simple but general soil model; and (ii) a general computational framework, enabling the development of efficient interactive software for the analysis of dynamic soil-structure interaction problems.With regard to the model, a general, non-associative, elasto-plastic soil model has been developed. An alternate volume change behavior of soils characterizing isotropic compression and extension with exponential and power laws respectively is proposed and included in the model. Distinct volumetric and distortional (shear) mechanisms are used based on double hardening concepts. An optimization scheme is used to estimate the model parameters using experimental results for a given soil. Essential features of sands such as path dependent dilatancy, hardening and softening, liquefaction, initial and induced anisotropy and that of clay are reproduced with unprecedented accuracy for a model of this simplicity.With regard to the computational framework, a general computational framework is presented based on object-oriented programming for the analysis of soil-structure interaction problems. Based on this framework, a prototype finite element program (SAND) has been developed implementing an iterative direct solution scheme, and a new kind of efficient interface element has been derived. Illustrative examples have been presented to verify the implementation of the prototype and to demonstrate the new capabilities of the interactive analysis.
Thesis (Ph. D.)--University of Washington, 1996
Keywords: Theses--Civil engineering